School variation in asthma: compositional or contextual? - Tracy K Richmond (Public Library of Science (PLoS), 2009)
Background Childhood asthma prevalence and morbidity have been shown to vary by neighborhood. Less is known about between-school variation in asthma prevalence and whether it exists beyond what one might expect due to students at higher risk of asthma clustering within different schools. Our objective was to determine whether between-school variation in asthma prevalence exists and if so, if it is related to the differential distribution of individual risk factors for and correlates of asthma or to contextual influences of schools. Methods Cross-sectional analysis of 16,640 teens in grades 7-12 in Wave 1 (data collected in 1994-5) of the National Longitudinal Study of Adolescent Health. Outcome was current diagnosis of asthma as reported by respondents' parents. Two-level random effects models were used to assess the contribution of schools to the variance in asthma prevalence before and after controlling for individual attributes. Results The highest quartile schools had mean asthma prevalence of 21.9% compared to the lowest quartile schools with mean asthma prevalence of 7.1%. In our null model, the school contributed significantly to the variance in asthma (sigma(u0)(2) = 0.27, CI: 0.20, 0.35). Controlling for individual, school and neighborhood attributes reduced the between-school variance modestly (sigma(u0)(2) = 0.19 CI: 0.13-0.29). Conclusion Significant between-school variation in current asthma prevalence exists even after controlling for the individual, school and neighborhood factors. This provides evidence for school level contextual influences on asthma. Further research is needed to determine potential mechanisms through which schools may influence asthma outcomes.